DOP006 A multicentre cohort study to assess the safety of vedolizumab for inflammatory bowel disease. (16th January 2018) - Meserve, J; Aniwan, S; Koliani-Pace, J L; Shashi, P; Weiss, A; Faleck, D; Winters, A; Chablaney, S; Kochhar, G; Boland, B; Singh, S; Hirten, R; et al.
Abstract: Background: We aimed to quantify rates and identify predictors of serious adverse events (SAE) with vedolizumab (VDZ) for Crohn's disease (CD) and ulcerative colitis (UC). Methods: This was a review of a multicentre, US-based consortium of CD and UC patients treated with VDZ. Serious infections (SI) were defined as those requiring antibiotics or hospitalisation, or resulting in discontinuation of VDZ or death. SAE were defined as SI or adverse events resulting in discontinuation of VDZ or death. Multivariable logistic regression analyses with odds ratio (OR) and 95% confidence intervals (CIs) are reported for independent predictors of SI and SAE. Results: 1087 patients ( n = 650 CD; 45% male) with a median follow-up of 302 days (interquartile range 171–434) were included. SI occurred in 66 patients (6%); the most common SI were C. difficile ( n = 24), abscess ( n = 11), respiratory tract infections ( n = 10), zoster ( n = 7), and bacteraemia ( n = 6). SAE occurred in 73 patients (7%), with no reported malignancies. Transverse myelitis ( n = 1) and optic neuritis ( n = 1) were the only two reported central nervous system adverse events. SI and SAE were observed in 3.7% and 4.3% of patients on VDZ monotherapy, 6.1% and 6.7% of patients on VDZ in combination with steroids or an immunomodulator (azathioprine, 6-mercaptopurine, methotrexate), and 9.8% and 10.7% of patients on VDZ in combination with both steroids and an immunomodulator. On multivariable analyses, after adjusting for inflammatory bowel disease type (CD vs. UC), age, and sex, concomitant immunosuppressive (steroid or immunomodulator) therapy was the only independent predictor of SI (OR 1.67 per number of immunosuppressive agents used, 95% CI 1.17–2.38) and SAE (OR 1.65 per number of immunosuppressive agents used, 95% CI 1.17–2.31). Conclusions: VDZ is well tolerated in clinical practice, with SI and SAE being reported in 6% and 7% of patients, respectively. The strongest predictor of SI or SAE is the use of concomitant steroids or immunomodulators, with the greatest risk seen in patients on triple therapy with VDZ, steroids, and immunomodulator therapy. Further studies are needed to identify patients who will most benefit from concomitant immunosuppressive therapy use with VDZ to optimise the safety profile in clinical practice.